Response of Induced Seismicity to Injection Rate Reduction: Models of Delay, Decay, Quiescence, Recovery, and Oklahoma. Issue 1 (28th January 2019) - Dempsey, David; Riffault, Jeremy
Abstract: When injection‐induced seismicity poses a risk to communities, it is common to reduce the injection rate or halt operations. This applies both to individual wells and well clusters, such as those within the Area of Interest for Triggered Seismicity in Western Oklahoma, where in 2016 a 40% volume reduction mandate was imposed by the state regulator. Here we quantify how induced seismicity responds to an injection reduction. We introduce models of pressure diffusion in idealized geometries coupled to steady state pressurization and rate‐state models of earthquake triggering. We find that the delay in seismicity onset and then postreduction behavior—decay, sometimes quiescence, and recovery of the seismicity rate—depend on the critical triggering pressure and on diffusion and rate‐state parameters. We have adapted our model to replicate the timing of onset, peak, and recent pace of decline of seismicity triggered by wastewater injection in Western Oklahoma. Our analysis implies that diffusivity in the Arbuckle formation is high (between 44 and 277 m 2 /s). The critical triggering pressure is inferred to be between 0.021 and 0.077 MPa, and fluid overpressure at 4.5‐km depth in the basement is estimated to have increased by as much as 0.190 MPa. We simulate future seismicity out to 2025 for three scenarios. Fixing the 2018 injection rate, already less than the limit imposed by the state regulator, we find a high likelihood of further M ≥ 5 earthquakes. This suggests that the volume reduction mandate in Western Oklahoma is, at present levels, inadequate. Key Points: We developed models of induced seismicity decay and recovery after an injection rate reduction Seismicity, dependent on pressurization rate above a threshold pressure, replicates Oklahoma events Current mandated volume reduction in Western Oklahoma is insufficient to prevent further M 5 events